Engineering of long-acting human growth hormone-Fc fusion proteins: Effects of valency, fusion position, and linker design on pharmacokinetics and efficacy. - Taekyeol Lee; Dongsop Lee; Eunee Jung; Mikyung Son; Kyohwan Koo; Jaehoon Choi (PLoS ONE)
Fc fusion proteins, formed by fusing an active protein to the Fc region of immunoglobulin G, are a validated strategy for extending the half-life of therapeutic proteins. Human growth hormone (hGH) Fc fusion proteins exhibit longer circulation half-lives than hGH, reducing injection frequency and improving convenience for hGH replacement therapy. Most approved Fc fusion proteins involve directly attaching the active protein to the hinge region of IgG Fc; however, few reports have described the effects of structural variations on these characteristics in detail. We analyzed pharmacokinetic and pharmacodynamic properties of various hGH-Fc fusion constructs differing in linker type, hGH valency, and fusion position to investigate the structure-function relationships of these proteins in cell-based assays and animal models, including normal and hypophysectomized rats. Monovalent hGH-Fc fusion variants and those with hGH fused to the C-terminal of IgG Fc exhibited higher in vitro and in vivo activity than bivalent hGH-Fc. However, these variants also exhibited accelerated clearance in rat pharmacokinetic experiments. The linker connecting the hGH moiety to the Fc domain significantly influenced in vitro activity and pharmacokinetics. Constructs with a rigid alpha-helical A(EAAAK)5A linker showed greater in vitro activity than those with a flexible (GGGGS)3 linker but exhibited accelerated clearance in rats. To a lesser extent, linker length influenced activity and pharmacokinetics. Bivalent hGH-Fc constructs with shorter linkers (0-1 GGGGS repeats) exhibited higher in vivo exposure (AUC) but lower in vitro activity than those with longer linkers (2-3 repeats). In vitro activity did not correlate linearly with linker length, as constructs with no linker (n = 0) showed reduced activity, while no consistent trend was observed for n = 1-3. These findings provide valuable insights into the design of hGH-Fc fusion proteins, offering a framework for systematically improving their potency and longevity and supporting the development of long-acting hGH therapies.